Improving primary school numeracy literacy through play interventions and home-school partnerships - Cucu Maryam; Rina Heryani (Universitas Pendidikan Indonesia, 2025)
Numeracy literacy is an essential basic skill for primary school students, including counting, understanding patterns, reading data, and applying mathematical concepts in everyday life. However, low interest in learning mathematics and limited parental involvement are challenges in strengthening numeracy literacy at the primary level. This study explores the effectiveness of play-based interventions and home-school partnerships in improving numeracy literacy in primary schools. The main reason for this research is to find fun learning strategies while encouraging active parental involvement to strengthen children's understanding of mathematical concepts. A qualitative approach with a case study design was used in this study involving teachers, low-grade students, and parents in an elementary school that implemented play-based learning and home-school collaboration. Data were collected through observation, in-depth interviews, and documentation. The results showed that game-based learning effectively improved students' motivation and understanding of mathematics concepts. In addition, parents' involvement in counting activities at home also strengthens students' learning outcomes. This research recommends the integration of fun and collaborative learning methods to improve the quality of basic education. Abstrak Literasi numerasi merupakan keterampilan dasar yang sangat penting bagi peserta didik sekolah dasar mencakup kemampuan berhitung, memahami pola, membaca data, hingga menerapkan konsep matematika dalam kehidupan sehari-hari. Namun, rendahnya minat belajar matematika dan keterbatasan keterlibatan orang tua menjadi tantangan dalam penguatan literasi numerasi di tingkat dasar. Penelitian ini bertujuan untuk mengeksplorasi efektivitas intervensi berbasis bermain dan kemitraan rumah-sekolah dalam meningkatkan literasi numerasi di sekolah dasar. Alasan utama penelitian ini yakni mencari strategi pembelajaran yang menyenangkan sekaligus mendorong keterlibatan aktif orang tua guna memperkuat pemahaman konsep matematika anak. Pendekatan kualitatif dengan desain studi kasus digunakan dalam penelitian ini melibatkan guru, peserta didik kelas rendah, dan orang tua di sekolah dasar yang menerapkan pembelajaran berbasis permainan serta kolaborasi rumah-sekolah. Data dikumpulkan melalui observasi, wawancara mendalam, dan dokumentasi. Hasil penelitian menunjukkan bahwa pembelajaran berbasis permainan efektif meningkatkan motivasi dan pemahaman konsep matematika peserta didik. Selain itu, keterlibatan orang tua dalam aktivitas berhitung di rumah turut memperkuat hasil belajar peserta didik. Penelitian ini merekomendasikan integrasi metode pembelajaran yang menyenangkan dan kolaboratif untuk meningkatkan kualitas pendidikan dasar. Kata Kunci: intervensi bermain; kemitraan rumah-sekolah; literasi numerasi; pembelajaran kolaboratif; pendidikan dasar